PENGARUH BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP HUBUNGAN ANTARA PARTISIPASI ANGGARAN DENGAN KINERJA MANAJERIAL - Hafsah, Ramdhansyah (Jurnal Riset AKuntansi dan Bisnis, 2009)
This study examines the influence of organizational culture and leadershipstyle as moderating variables on the relationship between budgetary participationand managerial performance. This study used employee oriented vs. job orienteddimension for organizational culture, and consideration and initiating structuredimensions for leadership style.Questionnaire survey were used and data were analyzed using moderatedregression model. The results of this study showed that budgetary participation has apositive effect on managerial performance. The results also showed thatorganizational culture moderates the relationship between budgetary participationand managerial performance. More specifically, job oriented organizational culturehas a negave influence to the relationship between budgetary participation andmanagerial performance. As for the leadership style, the results showed thatleadership style do not moderate the relationship between budgetary participationand managerial performance.